Implications of multimodal learning models for foreign language teaching and learning - Farías, Miguel; Obilinovic, Katica; Orrego, Roxana (Colombian Applied Linguistics Journal, 2007)
This literature review article approaches the topic of information and communications technologies from the perspective of their impact on the language learning process, with particular emphasis on the most appropriate designs of multimodal texts as informed by models of multimodal learning. The first part contextualizes multimodality within the fields of discourse studies, the psychology of learning and CALL; the second, deals with multimodal conceptions of reading and writing by discussing hypertextuality and literacy. A final section outlines the possible implications of multimodal learning models for foreign language teaching and learning.